Potential of Clay in Coal Mining of Tanjung Enim Area as a Filler on Rubber Compound. (February 2019) - Hasan, A; Kalsum, L; Yerizam, M; Junaidi, R; Taufik, M; Aznury, M; Fatria
Abstract: The clay deposit in the coal mining area of Tanjung Enim has a deposit about five times its coal deposit. This clay has not been utilized except as glue on brick briquettes which are relatively small quantities. As a rubber filler, clay can be used, but the silica content is preferred in the clay. Therefore the composition of silica in clay must be known. This study aims to determine the content of silica in the clay contained in the coal mining area of Tanjung Enim. The research begins with clay drying, followed by the fineness of clay grain size to a size of about 10-50 microns. Furthermore, the analysis of the compounds there in is carried out using XRF. The results show that the silica content in the clay is about 53.74 - 75.29% and the highest content is in the Lower D layer 75.29% and followed by the Int B2-C layer 56.87% and Lower C 56.65 %. In general, the compounds in this clay are dominated by SiO2, Al2 O3, Fe2 O3, MgO, TiO2, and K2 O.